(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper ,an analytical study of a conventional hydrodynamics bearing was carried out. An integrated program was built using a computer program and through the Matlab facility in order to solve Reynolds equation numerically using finite difference method and analytically through the short bearing theory.The effects of the thermal distortion on the bearing performance arestudied. The thermal distortion is a result of the temperature riseeffects. This study was carried out for journal speed 3000 rpm. The oil film pressure distribution is obtained by solving Reynolds equationnumerically and analytically.Pinkus’s approach has been used in computing the temperature distribution along the circumferential direction of the bearing surface. Analytical solution for Reynolds equation overestimates the bearing characteristics and Capacity compared with numerical solution results. It was found that THL effect the bearing performance positively (in the low range of temperature) by increasing stiffness and load capacity also it was found that using correction factor is useful to get more accurate assessment for the bearing performance by solving Reynolds equation analytically.